The Challenges of Corrosion Control on Metallic Surfaces (IntechOpen, 2026)
Metals deteriorate over time through chemical or electrochemical reactions with their environment, resulting in corrosion, a natural and often unavoidable process. Besides shortening the lifespan of metal parts, this phenomenon leads to significant financial costs, safety hazards, and maintenance challenges across various industries, including maritime engineering, transportation, construction, and the oil and gas sector. The enormous range of environmental variables to which metals are exposed, from saline water and acidic soils to industrial contaminants and air humidity, makes controlling corrosion a constant challenge. Additionally, it is challenging to implement a one-size-fits-all solution due to the varied compositions and surface properties of metallic materials. Although coatings, cathodic protection, alloying, and inhibitors are examples of traditional protective techniques that have demonstrated varied degrees of effectiveness, their environmental impact, longevity, and cost-effectiveness are frequently limited. The need for creative, long-lasting, and reliable corrosion management techniques is greater than ever, as contemporary applications require metal constructions to be more reliable and durable. This book presents research on corrosion and the challenges faced in controlling corrosion on metallic surfaces.